On Religious Freedom and Its Free Exercise - Gamwell, Franklin I. (The journal of religion, 2017)
The article examines freedom of religion in the U.S. as of September 2017. Topics include the political relevance of religion, the right to exercise religious conviction, and the 1993 Religious Freedom Restoration Act. Also discussed are the Supreme Court case involving Hobby Lobby Stores Inc. that dealt with free exercise, the possibility of free exercise exemptions in religious freedom, and democracy with religious freedom.